KEBIJAKAN KURIKULUM MERDEKA DAN IMPLEMENTASINYA DI SEKOLAH DASAR - Slamet Widodo; ‪Adhy Putri Rilianti‬; ‪Wulida Arina Najwa; ‪M. Misbachul Huda‬; Anang Fathoni (Journal of Professional Elementary Education, 2023)
The purpose of writing this article is to describe the independent curriculum policy and its implementation on campuses and elementary schools. The type of research used in this study is literature review research. The research approach used is in the form of systematic characteritic samples using sources of written works such as books, articles, policy documents, and other types of written works. The results of the analysis found that the independent learning policy document was 30 articles. This research procedure consists of 4 stages, including: (1) making designs, (2) conducting studies, (3) analyzing, and (4) compiling and writing results.  The results of the review are divided into 3, namely: (1) independent curriculum, (2) implementation of independent curriculum on educational campuses, and (3) implementation of independent curriculum in elementary schools. In the independent curriculum, there are several characteristics, including: changes in class hours and teaching teachers, strengthening the profile of Pancasila students, local content, teaching modules, project-based learning, learning outcomes formed phases hierarchically, independent teaching platforms, and curriculum structure. For educational campuses, with the independent curriculum policy, the campus needs to complete course materials with the needs of an independent curriculum, the campus needs to provide learning rights to students to study outside the study program, the campus needs to adjust changes in the definition of credits, and the campus needs to conduct a scheduled study tracer to measure the quality of performance. Each elementary school is free to determine the curriculum to be applied. Some of the tasks if elementary schools implement an independent curriculum are the application of Natural and Social Sciences, the integration of skills lessons in art lessons, and the application of school assessments